INVESTIGATION OF THE RELATIONSHIP BETWEEN ANXIETY STATUS OF NURSING STUDENTS AND THEIR COMMITMENT TO THE PROFESSION DURING COVID-19 PANDEMIC - ATEŞ, Sebahat; KAÇAN, Havva; AYHAN, Fatma; YÜKSEL, Azzet (INESEG Yayincilik, 2022)
This study examined the relationship between nursing students' anxiety and professional commitment during the Covid-19 pandemic process. This research used a descriptive and correlational research design; it was conducted in the fall semester of the 2020-2021 academic year when the pandemic process continued. The research was conducted with 1026 nursing students from two state and two private universities, these students who agreed to participate formed the sample of the research. Sociodemographic characteristics, questions about the Covid-19 Pandemic process, Beck Anxiety Scale and Nursing Professional Commitment Scale were used to collect data. Data were collected online. The 1st and 4th-year male students' professional commitment average whose grade poing average is below 2.00 was low (p
Keywords: Medicine (General); Sağlık Kurumları Yönetimi; anxiety; profession commintment; R5-920; covid-19; Health Care Administration; Nursing students; Covid-19; Profession Commintment; Anxiety; Public aspects of medicine; RA1-1270; nursing students; 4. Education; 3. Good health